PENGARUH KEADILAN, SOSIALISASI, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Fransisca Dyah Anggraini; Khairunnisa Khairunnisa (Universitas Indo Global Mandiri, 2022)
The purpose of this study is to determine whether justice, socialization and tax sanctions have influence on tax compliance. All restaurant and restaurant business taxpayers in Palembang is the population of this study. The sampling method in this study is purposive sampling. The restaurant and restaurant business taxpayers which stands more than a year is the sample of this study. The number of samples in this study is 62 respondents. Multiple regression analysis used to determine the effect of the variables of justice, socialization and tax sanctions have an effect on tax compliance. The results of this study showed that tax justice variable had no effect on tax compliance, while the socialization variable and tax sanctions had a significant effect on tax compliance.